Sunitinib followed by sorafenib or vice versa for metastatic renal cell carcinoma--data from the Czech registry - Buchler, T; Klapka, R; Melichar, B; Brabec, P; Dusek, L; Vyzula, R; Abrahamova, J (Annals of oncology, 2012)
BACKGROUND: Sequential therapy with tyrosine kinase inhibitors (TKIs), sunitinib and sorafenib, is a common treatment choice for patients with advanced/metastatic renal cell carcinoma (mRCC) despite lack of randomised trials. The aim of this retrospective registry-based study was to analyse the outcomes of RCC patients treated with sunitinib-sorafenib or sorafenib-sunitinib sequence. PATIENTS AND METHODS: The Czech database containing information on patients treated for mRCC using targeted agents was used as a source of data for retrospective analysis. There were 138 patients treated with sunitinib-sorafenib sequence and 122 patients treated with sorafenib-sunitinib sequence. RESULTS: Progression-free survival (PFS) was 17.7 months for patients treated with sunitinib-sorafenib sequence and 18.8 months for those receiving sorafenib followed by sunitinib (P = 0.47). Overall survival (OS) at 1 year was 83% [95% confidence interval (CI) 77% to 90%] for patients treated with sunitinib-sorafenib and 84% (95% CI 77% to 91%) for sorafenib-sunitinib patients (P = 0.99). Treatment toxic effects were predictable but a significant proportion of patients (up to 14%-25% for different lines of therapy and used TKI) switched between TKIs or discontinued TKI therapy because of toxicity. CONCLUSIONS: In contrast to most of the previously published reports, we have not observed improved PFS or OS for mRCC patients treated with the sorafenib-sunitinib sequence as compared to the sunitinib-sorafenib sequence.
Keywords: senioři; Sorafenib; Phenylurea Compounds; Carcinoma, Renal Cell; Indoles; Sunitinib; Protein Kinase Inhibitors; Niacinamide; Benzenesulfonates; Retrospective Studies; lidé; niacinamid; Protein-Tyrosine Kinases; výsledek terapie; Middle Aged; Drug Administration Schedule; registrace; mužské pohlaví; Pyridines; pyridiny; sorafenib; nádory ledvin; karcinom z renálních buněk; Adult; sunitinib; Registries; Kidney Neoplasms; Pyrroles; ženské pohlaví; retrospektivní studie; Humans; lidé středního věku; tyrosinkinasy; rozvrh dávkování léků; Antineoplastic Combined Chemotherapy Protocols; indoly; inhibitory proteinkinas; protokoly protinádorové kombinované chemoterapie; dospělí; benzensulfonáty; Female; Aged; Treatment Outcome; pyrroly; Male; fenylmočovinové sloučeniny